Step * 2 1 1 1 of Lemma rexp-positive


1. : ℝ
2. : ℝ
3. r0 ≤ z
4. r0 ≤ (z y)
5. r1 ≤ e^z
6. r0 < e^z
7. ((z y) -(z))
⊢ r0 < (e^z e^-(z))
BY
(FLemma `rexp-of-nonneg` [4] THENA Auto) }

1
1. : ℝ
2. : ℝ
3. r0 ≤ z
4. r0 ≤ (z y)
5. r1 ≤ e^z
6. r0 < e^z
7. ((z y) -(z))
8. r1 ≤ e^z y
⊢ r0 < (e^z e^-(z))


Latex:


Latex:

1.  y  :  \mBbbR{}
2.  z  :  \mBbbR{}
3.  r0  \mleq{}  z
4.  r0  \mleq{}  (z  +  y)
5.  r1  \mleq{}  e\^{}z
6.  r0  <  e\^{}z
7.  y  =  ((z  +  y)  +  -(z))
\mvdash{}  r0  <  (e\^{}z  +  y  *  e\^{}-(z))


By


Latex:
(FLemma  `rexp-of-nonneg`  [4]  THENA  Auto)




Home Index